Characterizing the Data in Online Companion-dog Obituaries to Assess Their Usefulness as a Source of Information about Human–Animal Bonds. (1st September 2016) - MacKay, Jill R. D.; Moore, Janice; Huntingford, Felicity
ABSTRACT: Online pet obituary sites host hundreds of obituaries regarding the passing of companion animals. Often composed by the owner or primary caretaker of the animal, they are a potential source of data about human–animal bonds where there were strong positive human emotions surrounding the animal at point of death. The aim of the present study was to characterize on-line pet obituaries and to evaluate their usefulness as a source of information on the human–animal bond. One hundred and thirty full obituaries of dogs were studied. Where the role of the writer could be identified, the majority of obituary writers identified themselves as a female parental figure to the dog (34.6%); however, obituaries were also written by male parental figures (7.7%) and children (5.4%). Most obituaries (60%) fell within the 100-400 words length range. Obituaries were seen to express several key concepts. For instance, dogs were described as "child-like, " "part of the family, " showing "sympathy" and/or "gratitude" to the owner, and having a "sense of humor." For their part, writers expressed "guilt" over the dog's death, discussed a concept of the "afterlife" and noted an "instant connection" between themselves and the dog. A high proportion of the obituaries discussed the afterlife (51%) and indicated that the dog was considered part of the family (49%). There were some significant associations between concept usage within obituaries. Dogs that were described as "child-like" were more often perceived to be in an "afterlife" and to have had an "instant connection" with obituary writers (x 2 = 38.08, p < 0.001). We conclude that online pet obituaries can be a valuable source of information on human feelings surrounding a companion animal death.